Giamblico, De anima : i frammenti, la dottrina - Martone, Lucrezia Iris (Greco, arabo, latino. Studi, 2013)
In recent years, the attention of scholars to the figure and work of Iamblichus has increased, while the emphasis is on his thought in the history of the Platonic school. However, a major work still remains to be studied: the De Anima . Preserved only in fragments in the anthology of Stobaeus, it proves to be of crucial importance for the understanding of the development of Platonism at the end of antiquity.